Rewetting and Drainage of Nutrient-Poor Peatlands Indicated by Specific Bacterial Membrane Fatty Acids and a Repeated Sampling of Stable Isotopes (δ15N, δ13C) - Groß-Schmölders, Miriam; Klein, Kristy; Birkholz, Axel; Leifeld, Jens; Alewell, Christine (Frontiers in Environmental Science, 2021)
Peatland degradation impairs soil functions such as carbon storage and the existence of biodiversity hotspots. Therefore, and in view of the ongoing climate change, an efficient method of evaluating peatland hydrology and the success of restoration efforts is needed. To understand the role of microbial groups in biogeochemical cycling, gaseous loss and isotopic fractionation that lead to specific isotopic depth patterns (δ13C, δ15N), we integrated previously published stable isotope data with a membrane fatty acid (mFA) analysis related to various microbial groups that are known to be common in peatlands. We performed two sampling campaigns to verify the observed stable isotope depth trends in nutrient-poor peatlands in Northern Europe. Cores were taken from adjacent drained (or rewetted) and undrained sites. Fungal-derived mFA abundance was highest in the uppermost part of the drained layer. We found increasing bacterial-derived mFA concentrations with depth peaking in the middle of the drained layers, which correlates with a δ15N peak of bulk material. The results support our hypothesis that bacteria are main decomposers in deeper, facultative anaerobic to anaerobic layers. However, under waterlogged conditions overall levels of microbial-derived mFAs were generally low. These results are congruent with the stable isotope depth pattern. For example, bacteria, particularly acidobacteria, can be expected to dominate increased denitrification with the absence of oxygen accompanied by increased isotopic fractionation. Thus, increased anaerobic microbial activity is reflected by increased δ15N and δ13C values. In contrast, cores from rewetted peatlands show no depth trend of δ15N in the layers grown under rewetting conditions; this is congruent with relatively low concentrations of microbial-derived mFAs. We conclude that stable isotopes, especially δ15N values, reflect microbial metabolic processes, which differ between drained, rewetted and undrained peatlands and thus could indicate both drainage and restoration success.